2009
DOI: 10.1016/j.jaci.2009.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin deficiency confers a paracellular barrier abnormality that reduces inflammatory thresholds to irritants and haptens

Abstract: Background Mutations in filaggrin (FLG) are associated with atopic dermatitis (AD), and are presumed to provoke a barrier abnormality. Yet, additional acquired stressors may be necessary, since the same mutations can result in a non-inflammatory disorder, ichthyosis vulgaris. Objective We examined here whether FLG deficiency alone suffices to produce a barrier abnormality; the basis for the putative abnormality; and its pro-inflammatory consequences. Methods Using the flaky-tail (ft/ft) mouse, which lacks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
236
3
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(265 citation statements)
references
References 62 publications
18
236
3
8
Order By: Relevance
“…Mice of the Flg ft genotype express an abnormal profilaggrin polypeptide that does not form normal keratohyalin F-granules and is not proteolytically processed to filaggrin. Therefore, filaggrin is absent from the cornified layers in the epidermis of the Flg ft mouse (Fallon, et al, 2009, Presland, et al, 2000, Scharschmidt, et al, 2009). Consistently, we and others have described that Flg ft mice express a truncated and smaller profilaggrin protein that is not processed to filaggrin (Fallon, et al, 2009, Moniaga, et al, 2010, Presland, et al, 2000 (Fig.1).…”
Section: Origin Of Flaky Tail Micementioning
confidence: 99%
See 2 more Smart Citations
“…Mice of the Flg ft genotype express an abnormal profilaggrin polypeptide that does not form normal keratohyalin F-granules and is not proteolytically processed to filaggrin. Therefore, filaggrin is absent from the cornified layers in the epidermis of the Flg ft mouse (Fallon, et al, 2009, Presland, et al, 2000, Scharschmidt, et al, 2009). Consistently, we and others have described that Flg ft mice express a truncated and smaller profilaggrin protein that is not processed to filaggrin (Fallon, et al, 2009, Moniaga, et al, 2010, Presland, et al, 2000 (Fig.1).…”
Section: Origin Of Flaky Tail Micementioning
confidence: 99%
“…Later, the lack of filaggrin in the epidermis was proposed in the commercially available strain of Flg ft mice, which has both Flg and ma mutations, as a model of IV, and therefore there was no discussion about the cutaneous inflammatory conditions from the perspective of AD (Presland, et al, 2000). There have been four recent papers of Flg ft mice as a model of filaggrin deficiency: the first paper used Flg ft mice from which the ma mutation had been eliminated with four additional backcrosses to B6 mice (Fallon, et al, 2009), and the others used the commercially available Flg ft mice (Moniaga, et al, 2010, Oyoshi, et al, 2009, Scharschmidt, et al, 2009). The first report showed only histological abnormality without clinical manifestation (Fallon, et al, 2009), and the second demonstrated spontaneous eczematous skin lesions after 28 weeks of www.intechopen.com age (Oyoshi, et al, 2009), and the third contained no notice of any spontaneous dermatitis in Flg ft mice (Scharschmidt, et al, 2009).…”
Section: Flaky Tail Mouse In a Steady Statementioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that filaggrin (FLG) is a main protein which produces the NMF in the stratum corneum, and bears the water-retention ability of the stratum corneum [3]. FLG is a protein of epidermal keratinocytes; at first, a precursor of proFLG was made in the cells of the granular cell layer, which becomes the principal ingredient of keratohyalin granules [4]. When the keratinocyte of the granular cell layer turns into the stratum corneum, it is decomposed and the proFLG turns into FLG [4].…”
Section: Introductionmentioning
confidence: 99%
“…FLG is a protein of epidermal keratinocytes; at first, a precursor of proFLG was made in the cells of the granular cell layer, which becomes the principal ingredient of keratohyalin granules [4]. When the keratinocyte of the granular cell layer turns into the stratum corneum, it is decomposed and the proFLG turns into FLG [4]. FLG has the action which condenses the keratin fiber of the keratinocyte.…”
Section: Introductionmentioning
confidence: 99%